Characterization of a Newly Isolated Marine Fungus Aspergillus dimorphicus for Optimized Production of the Anti-Tumor Agent Wentilactones - Xu, Rui (Mar Drugs, 2015)
The potential anti-tumor agent wentilactones were produced by a newly isolated marine fungus Aspergillus dimorphicus. This fungus was derived from deep-sea sediment and identified by polyphasic approach, combining phenotypic, molecular, and extrolite profiles. However, wentilactone production was detected only under static cultures with very low yields. In order to improve wentilactone production, culture conditions were optimized using the response surface methodology. Under the optimal static fermentation conditions, the experimental values were closely consistent with the prediction model. The yields of wentilactone A and B were increased about 11-fold to 13.4 and 6.5 mg/L, respectively. The result was further verified by fermentation scale-up for wentilactone production. Moreover, some small-molecule elicitors were found to have capacity of stimulating wentilactone production. To our knowledge, this is first report of optimized production of tetranorlabdane diterpenoids by a deep-sea derived marine fungus. The present study might be valuable for efficient production of wentilactones and fundamental investigation of the anti-tumor mechanism of norditerpenoids.